Interactive learning media: Literacy and numeracy Limas House Balaputera Dewa Museum in phase B - Siti Dewi Maharani; Ratu Ilma Indra Putri; Ayu Fitriyanti Syawaliyah; Mazda Leva Okta Safitri (Universitas Muhammadiyah Malang, 2024)
Literacy and numeracy in Indonesia was still relatively low, teachers did not discuss literacy and numeracy material with students. Learning media needed to deliver material, but technology based learning media for literacy and numeracy materials had not been used in the learning process. This research aimed to determine the procedures for making products, the level of validity and practicality in literacy and numeracy material. The model used the ADDIE (Analysis, Design, Development Implementation and Evaluation) development model. Data collection techniques, including observation, interviews, questionnaires, and documentation. Data analyzed in two ways, namely qualitatively and quantitatively. Validation of the media is carried out by validating material experts, media experts and classroom teacher practitioner. The assessment results from material experts were 3.81 (very valid), media experts were 3.67 (very valid) and classroom teacher practitioner were 3.44 (very valid). Practicality was carried out with a total of 19 grade 4 students through three stages, namely one to one, small group trials and field test. The average score obtained was 89%, including the